(untitled) (Research, Society and Development, 2021)
The present work discusses and presents results of an experiment carried out in the Algorithms and Programming component of the Professional Technical Course in Systems Development of a public school, using the active learning methodology Peer Instruction (Peer Instruction). The teaching practice aims to develop the active and protagonist participation of students during Algorithms and Programming classes, through an active teaching method, in which it develops collaborative methods, allowing the socialization of knowledge in a short time, facilitating training necessary for students of professional technical education, so that in the future they can put their skills, abilities and attitudes into practice. The quick interaction offered by the Socrative Application, through diagnostic activities, at which time the teacher will identify the learning gaps, facilitating the resumption of the contents of the technological bases during the teaching and learning process. In this perspective, it is considered that we have achieved School Success.